Development of a Vacuum Machine for Separating Cutting Oil from Metal Waste by Utilising a Magnetic Inductive Sensor - Nicdananto, Habibie Ahmad; Zulkipli, Muhammad Asyraf Bin (SM Institute, 2025)
In response to the challenges of managing metal waste mixed with cutting oil in the manufacturing industry, this study presents the development of a vacuum machine designed to improve the efficiency of waste separation. By utilizing a magnetic inductive sensor as the primary detection component, the system is capable of identifying and separating metal waste from cutting oil during the vacuum process. The machine collects the waste mixture through a flexible hose and directs it into a separation chamber, where the sensor detects the presence of metal for accurate separation. The development methodology includes design prototyping, testing under various waste conditions, and evaluating the sensor's performance and overall separation efficiency. Experimental results show that the system effectively detects metal particles and facilitates the separation process, with performance influenced by the volume, flow behavior, and metal concentration in the waste. These findings highlight the potential of sensor-based automation to optimize industrial waste handling. Overall, the study contributes to sustainable manufacturing practices by enabling more precise and efficient separation of metal waste contaminated with cutting oil.